The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14063592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using Green Concrete Materials on the CO2 Emissions of the Residential Building Sector in Egypt

Abstract: Increasing the rate of construction material consumption has caused significant environmental problems in recent decades, especially the production of ordinary Portland cement (OPC), which has been associated with 8% of the world’s human CO2 emissions and is considered the leading binder of concrete. This study aims to investigate the effects of substituting conventional concrete (CC) material with green concrete (GC) in the non-structural concrete works of a residential building in New Borg El-Arab City, Egyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Jonkute et al 23 analyzed the carbon dioxide emission of residential buildings in Lithuania, through the energy performance certification. A similar study in Egypt can be found in Marey et al 24 . Luo et al 25 studied the carbon emission for the renovation of old residential areas through a life cycle assessment.…”
Section: Literature Reviewsupporting
confidence: 80%
“…Jonkute et al 23 analyzed the carbon dioxide emission of residential buildings in Lithuania, through the energy performance certification. A similar study in Egypt can be found in Marey et al 24 . Luo et al 25 studied the carbon emission for the renovation of old residential areas through a life cycle assessment.…”
Section: Literature Reviewsupporting
confidence: 80%
“…Due to the high content of lignin, its strength and resistance to decay are much better than that of straw, husks, sawdust and others. In addition, the walnut shell has the lowest water absorption among the listed materials [ 20 ]. Analyzing the above, we can confidently say that the walnut shell is a potentially interesting material for use as a partial replacement for coarse mineral aggregate in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Tere was a huge availability of volcanic scoria in lots of countries, but its low value and the pressure towards greater sustainable construction have ended in renewed interest in volcanic scoria as natural pozzolan for concrete. Te use of locally available cementing alternatives to produce green concrete has the advantage of the cost of concrete production in construction [17][18][19][20][21][22][23]. Natural volcanic scoria materials have been investigated in some parts of the world for their potential use as binding alternatives, fne aggregates, and coarse aggregates, and had been found to enhance some of the engineering properties of paste, mortar, and concrete.…”
Section: Introductionmentioning
confidence: 99%